2023
DOI: 10.3390/ijms24087675
|View full text |Cite
|
Sign up to set email alerts
|

Skin Microbiome in Prurigo Nodularis

Abstract: Prurigo nodularis (PN) is a chronic condition characterized by the presence of nodular lesions accompanied by intense pruritus. The disease has been linked to several infectious factors, but data on the direct presence of microorganisms in the lesions of PN are scarce. The aim of this study was to evaluate the diversity and composition of the bacterial microbiome in PN lesions by targeting the region V3-V4 of 16S rRNA. Skin swabs were obtained from active nodules in 24 patients with PN, inflammatory patches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Importantly, S. aureus -derived virulence factors are associated with AD skin inflammation, including phenol soluble modulin-α, proteases, superantigens, and delta toxin ( 5 8 ). A recent study found that S. aureus was predominant in the microbiome of prurigo nodularis (PN) patients, which was highly similar to AD patients ( 9 ). In bullous pemphigoid (BP), S. aureus colonization was observed in 85% of patients and antibiotic treatment resulted in clinical improvement ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Importantly, S. aureus -derived virulence factors are associated with AD skin inflammation, including phenol soluble modulin-α, proteases, superantigens, and delta toxin ( 5 8 ). A recent study found that S. aureus was predominant in the microbiome of prurigo nodularis (PN) patients, which was highly similar to AD patients ( 9 ). In bullous pemphigoid (BP), S. aureus colonization was observed in 85% of patients and antibiotic treatment resulted in clinical improvement ( 10 , 11 ).…”
mentioning
confidence: 99%